Undercover lung damage in pediatrics - a hot spot in morbidity caused by collagenoses - Lupu, Ancuta; Sasaran, Maria Oana; Jechel, Elena; Azoicai, Alice; Alexoae, Monica Mihaela; Starcea, Iuliana Magdalena; Mocanu, Adriana; Nedelcu, Alin Horatiu; Knieling, Anton; Salaru, Delia Lidia; Burlea, Stefan Lucian; Lupu, Vasile Valeriu; et al. (Frontiers in Immunology, 2024)
Connective tissue represents the support matrix and the connection between tissues and organs. In its composition, collagen, the major structural protein, is the main component of the skin, bones, tendons and ligaments. Especially at the pediatric age, its damage in the context of pathologies such as systemic lupus erythematosus, scleroderma or dermatomyositis can have a significant negative impact on the development and optimal functioning of the body. The consequences can extend to various structures (e.g., joints, skin, eyes, lungs, heart, kidneys). Of these, we retain and reveal later in our manuscript, mainly the respiratory involvement. Manifested in various forms that can damage the chest wall, pleura, interstitium or vascularization, lung damage in pediatric systemic inflammatory diseases is underdeveloped in the literature compared to that described in adults. Under the threat of severe evolution, sometimes rapidly progressive and leading to death, it is necessary to increase the popularization of information aimed at physiopathological triggering and maintenance mechanisms, diagnostic means, and therapeutic directions among medical specialists. In addition, we emphasize the need for interdisciplinary collaboration, especially between pediatricians, rheumatologists, infectious disease specialists, pulmonologists, and immunologists. Through our narrative review we aimed to bring up to date, in a concise and easy to assimilate, general principles regarding the pulmonary impact of collagenoses using the most recent articles published in international libraries, duplicated by previous articles, of reference for the targeted pathologies.